2022
DOI: 10.3390/vaccines10081250
|View full text |Cite
|
Sign up to set email alerts
|

South African University Staff and Students’ Perspectives, Preferences, and Drivers of Hesitancy Regarding COVID-19 Vaccines: A Multi-Methods Study

Abstract: COVID-19 vaccine hesitancy poses a threat to the success of vaccination programmes currently being implemented. Concerns regarding vaccine effectiveness and vaccine-related adverse events are potential barriers to vaccination; however, it remains unclear whether tailored messaging and vaccination programmes can influence uptake. Understanding the preferences of key groups, including students, could guide the implementation of youth-targeted COVID-19 vaccination programmes, ensuring optimal uptake. This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Sociodemographic indicators of hesitancy mirror those found in other South African studies [ 19 , 38 , 39 , 40 ], which found that males and the younger cohort were less likely to vaccinate. In our study, doctors and other HCWs displayed higher levels of hesitancy compared to nurses.…”
Section: Discussionsupporting
confidence: 74%
“…Sociodemographic indicators of hesitancy mirror those found in other South African studies [ 19 , 38 , 39 , 40 ], which found that males and the younger cohort were less likely to vaccinate. In our study, doctors and other HCWs displayed higher levels of hesitancy compared to nurses.…”
Section: Discussionsupporting
confidence: 74%
“…With only 51% of the South African adult population vaccinated by the end of January 2023 21 and with research suggesting that HCWs remain a trusted source of information in their communities, [27][28][29] it is evident that HCWs have not been adequately educated and utilised in the promotion of vaccination. The literature highlights HCWs' pervasive sub-optimal knowledge and communication skills around COVID-19 vaccination, which has negatively impacted interactions with patients 30 and possibly affected vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events (AEs) resulting from repeated COVID-19 vaccine booster doses have become a significant area of research [1][2][3][4]. While vaccines remain one of the most effective means to prevent diseases, vaccine-related adverse events have always been a concern for the public [5][6][7]. Recent studies from large pharmacovigilance databases indicate substantial variability in adverse event incidence rates, emphasizing the need for context-specific analysis in vaccine safety surveillance to maintain public trust and inform future vaccination strategies [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%